Kuat Tekan Beton Dengan Penambahan Superplasticizer 0.25% dan Air Entraining Admixture 0.01%, 0.10%, 0.15% Menggunakan Mix Design Beton Mutu fc 25MPa - DAROJAT, ALFIYAN TAZKI (Universitas Negeri Surabaya, 2023)
This paper aims to determine the compressive strength of cylindrical concrete with mixed quality design fc 25Mpa with extra Air Entraining Addmixture to determine the effect of the added material on the compressive strength of concrete. Based on brochure Air Entraining, this additive is in nature polymer which dissolves in water which functions to increase the weight of the concrete and reduce the use of cement in the mixture. The concrete mix trials were divided into three treatments/three compositions, namely with Air Entraining 0.01%, 0.1% and 0.15% respectively by weight of cement. Thecomposition of the concrete mixture in each mix design composed of 18.48 kg of cement, 42.7 kg of fine aggregate, 22.14 kg of coarse aggregate of 5-12 mm size, 41.10 kg of coarse aggregate of 10-20 mm size, 5.98 kg of water. Compressive strength test results on cylindrical concrete with added materials Air Entraining 0.15% at 28 days of age of 17.00 MPa. Compressive strength of cylindrical concrete with additives Air Entraining 0.10% at 28 days of age of 18.75 MPa. Furthermore, for the compressive strength of cylindrical concrete with added materials Air Entraining 0.01% at 28 days of age of 26.10 MPa.